2013
DOI: 10.14578/jkfs.2013.102.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Physiological Characteristics of Pinus densiflora Seedlings in Response to Open-field Experimental Warming using the Infrared Lamp

Abstract: 요 약: 기후변화는 수목의 생장과 생리적 특성에 영향을 미칠 것으로 예상되고 있다. 본 연구는 인위적 온난화에 의한 소나무 묘목의 생장과 생리적 반응을 알아보기 위한 목적으로 수행되었다. 이를 위하여 2010년 4월 고려대학 교 구내 묘포장에 1년생 소나무 묘목을 식재하고 당해 11월부터 적외선등을 이용하여 3 o C 온도를 증가시키는 온난 화 처리를 하였으며, 2011년부터 3월부터 2013년 3월까지 묘고 및 근원경, 지상부 및 지하부 생물량, 잎의 엽록소 함량 및 질소 농도 등을 측정하였다. 묘고와 근원경의 경우 2012년 6월에 측정한 근원경을 제외하고 온난화 처리구 와 대조구간 유의한 차이를 보이지 않았다. 그러나 2013년 묘목 개체당 잎의 생물량은 온난화 처리구(23.94±2.10 g) 에서 대조구(26.08±1.72 g)보다 낮게 나타났으며, 줄기와 뿌리의 생물량 비율(S/R율)은 2013년에 온난화 처리구(1.09 ±0.07)에서 대조구(1.31±0.10)보다 낮게 나타났다. 한편 잎의 엽록소… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…These results were analogous to previous findings at the same study site, which found that warming had no effect on TRB and FRP of P. densiflora seedlings [23,28]. The absence of the warming effects on FRP, FRM, and root biomass might result from physiological adaptations of leaves to heat and drought stresses.…”
Section: Effect Of Warmingsupporting
confidence: 90%
“…These results were analogous to previous findings at the same study site, which found that warming had no effect on TRB and FRP of P. densiflora seedlings [23,28]. The absence of the warming effects on FRP, FRM, and root biomass might result from physiological adaptations of leaves to heat and drought stresses.…”
Section: Effect Of Warmingsupporting
confidence: 90%
“…Consistent with the different growth responses observed among species in this study, other species of the genera Pinus and Abies showed different growth responses following warming (Wang et al, 1995;Tjoelker et al, 1998;Zhao and Liu, 2009a;Wang et al, 2012;Yang et al, 2013). While RCD, seedling height, and total biomass of first-year P. densiflora increased under warming in this study, those of 2-4-year-old P. densiflora were not found to differ in response to warming in a previous study (Lee et al, 2013). This discrepancy might result from the effect of the growth stage and ontogenetic drift (Saxe et al, 2001).…”
Section: Growth Responsessupporting
confidence: 88%
“…P. densiflora can endure drought and barrenness, is an excellent pioneer species for secondary succession, and, thus, is crucial for reforestation and soil and water conservation [30]. The seed propagation of P. densiflora can be used for reforestation in the steeper barren hills.…”
Section: Introductionmentioning
confidence: 99%